Analysis of Technological Pedagogical Content Knowledge (TPACK) Ability for Prospective Chemistry Teacher Students and Chemistry Teachers: A Literature Review - Raihanah, Dinnah; Putri, Nabilah Mustika; Fatmawati, Tri Kurnia; Nurjayadi, Muktiningsih (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2024)
Mastering ICT is a prerequisite for teachers in the 21st century, and this is consistent with the TPACK framework that a teacher or aspiring teacher needs to be equipped with. Technological, pedagogical, and content knowledge (TPACK) is a conceptual framework that combines components that include three types of knowledge that teachers need to master, namely technological, pedagogical, and content knowledge. TPACK is a framework that seeks understanding the relationship between pedagogical and technological knowledge. In TPACK, teachers' knowledge of integrating technology into learning makes learning effective and efficient. This study aimed to observe the Technological Pedagogical Content Knowledge (TPACK) ability of prospective chemistry teachers and chemistry teachers. The research method used a literature study in the form of an analysis of various literature derived from national and international articles in accordance with the research objectives, namely 33 articles on the ability of Technological Pedagogical Content Knowledge (TPACK) of prospective chemistry teachers and chemistry teachers. The results showed that the components of TK, PK, TPK, TCK, and TPACK owned by prospective chemistry teachers and chemistry teachers were in the sufficient category. The TPACK abilities of chemistry teacher candidates and chemistry teachers still need to be improved in several aspects of content mastery, pedagogy, and technology. Developing TPACK abilities requires a long process to acquire new sources of skills and knowledge needed to form professional teachers.